Development of Mathematical Models for Trucks and Cargo - Larisa Makhova; Mark Haykin; Irina Glazkova; Olga Domnina (Infrastructures, 2023)
International trade allows countries to expand their markets and access goods and services that otherwise may not have been domestically available. As a result of international trade, the market is more competitive. This ultimately results in more competitive pricing and brings a cheaper product home to the consumer. The development of mathematical models to optimize the delivery of goods using a limited number of trucks is an urgent task for researchers around the world. The research goal was to use a developed mathematical model that allows one to optimize the performance of transportation tasks based on the selected parameters, both in terms of a particular truck and a fleet of trucks in the Russian region. The parameters (function, condition, cost, time, and quality) were set and an algorithm for the process of matching a specific truck and cargo was developed as part of the unit transportation task. A mathematical model has been developed for performing multiple freight tasks and operating a fleet of trucks, which considering such factors as cost, time, quality, and reputation, allows one to find an acceptable solution for a specific transportation task. A mathematical model was developed that considers such factors as cost, time, quality, and reputation, allowing one to find an acceptable solution for a particular transportation task. The simulation was performed in MATLAB 2018. The parameters of the simulations were a population size of 300, a maximum number of iterations of 2000, and a probability of selection of 0.85. From the 30 runs, the optional value was chosen as the best solution. The developed mathematical models have been tested for solving single and multiple transport problems under truck fleet simulation conditions. The results of the work can be used to optimize the operation of truck fleets in the Russian Federation and other countries.